Aplikasi Sistem Iformasi Akademik (SIAKAD) Dalam Perspektif Technology Acceptance Model - Indra Caniago; M. Rafiq M. Rafiq (Jurnal Ekonomi dan Manajemen, 2019)
The purpose of this study is to explore the effect of using the SIAKAD application with the technology acceptance model (TAM) approach. The variables used are perceived ease of use, perceived usefulness, behavioral intention and actual usage of the SIAKAD. The number of respondents in the study is 297 students of IBI Darmajaya. Software Lisrel is used to test the SEM model. The results of the analysis show the perceived ease of use and usefulness of using the SIAKAD application influence the students' behavioral intentions and the actual usage of the SIAKAD application. However, the behavioral intention does not affect the actual usage of the SIAKAD application. The effect of perceived ease of use and usefulness is greater on behavioral intention than the effect on actual usage of the SIAKAD application. The perceived ease of use has the greatest influence on the usefulness of using the SIAKAD application. The TAM model can analyze the technology acceptance behavior well. The TAM model helps prove that the behavioral use of required technology is only influenced by the perceived ease of use and the usefulness of the technology. The behavior of using the technology is not based on the intention of the user.